The Pleistocene and Stone Age of the Orontes River (Syria) - van Liere, Willem J.
1. Introduction and Summary; 2. The Late Villafranchian Level (QIIa); 3. The Middle Pleistocene Level (QIIb); 4. The Young Pleistocene Level (QIIIa); 5. The Young Pleistocene Orontes. Second Half (QIIIb); 6. The Holocene Orontes (QIV); 7. The Stratigraphy and Prehistory of the Orontes Equated with the Jordan and the Mediterranean Strand Levels; ersch. 1967; ٧-١٣ arabisch.